Single center experience of urinary bladder malignancy: a 10-year retrospective analysis of hospital data - T. P., Rajeev; Singh, Yashasvi; Barua, Sasanka Kumar; Sarma, Debanga (International Surgery Journal, 2017)
Background: Albeit the EAU, NCCN and AUA guidelines provide an excellent evidence-based protocol for the management of MIBC and NMIBC, these guidelines differ with respect to critical issues such as risk level definitions and management strategies. The NE part of the country has always bore the brunt of heavy oncological catastrophe like urinary bladder carcinoma related to extensive tobacco and pesticide usage. MIBC treatment usually encompasses RC with AC/NAC (Level I evidence for NAC use in MIBC exist) but the majority of patients seen at our center have already progressed to advanced stage at presentation and could not undertake full treatment. Methods: Cancer registry of the last 10 yrs at Dept. of Urology and Renal Transplant Gauhati Medical College Hospital was searched for demographic, clinical, pathological and prognostic data and results summarized using statistical parameters of univariate analysis. Results: There were a total of 168 patients in the NMIBC group with a majority in the 60-70-year age group. The most common grade was G2 and all DM type 2 and CKD were significantly associated in all the patients analyzed. Chemical exposure in the form of pesticide and smoking was a constant phenomenon in all patients of NMIBC and MIBC (n=66) population. CKD was significantly associated in the MIBC population along with positive urine cytology. Conclusions: Despite a paucity of high level evidence regarding the majority of management topics in Urinary Bladder cancer in NE part of the country, there was general agreement among the various guideline panels and management guidelines at our institution. Identification of the upfront clinical parameters suggesting severity of disease and time to progression are the two most important domains which will decide the future of UB carcinoma treatment in this part of the world. Categories of evidence synthesized and grades of recommendations will have to be constantly gazed upon to modify and enhance treatment strategies.